Teacher's attitudes towards use of ICT in preschool / Nursabeeha Abd Manap - Abd Manap, Nursabeeha (2013)
ICT has a great potential for enriching learning experience especially in early childhood education. Th need to integrate ICT at preschool level has become greater. The teacher as a mediator influences the use of ICT in teaching and learning. This study analysed the teachers' attitudes toward the use of ICT in teaching and learning in preschool. The aim of this study is to investigate teachers' attitudes toward the use of ICT and examine whether there are a relationship between teachers' attitudes with teachers' background (age, years of teaching experience and computer ownership).